Penambahan Kapasitas Jaringan Transmisi IPA Roban Kota Singkawang - Bambang Susmiyarto; Nurhayati Nurhayati; Marsudi Marsudi (Universitas Tanjungpura, 2022)
Singkawang City experiences a shortage of clean water during the dry season, especially in riverbanks. The Pajintan Reservoir is prepared to be used as a source of raw water for Singkawang City. This study aims to examine the addition of raw water capacity at the Roban WTP to fulfill clean water needs in Singkawang City during the dry season. The data used are rainfall and climate data from 2003 to 2017. River discharge is measured at the Sibuhe intake. The availability of water in the Sibuhe watershed was calculated using the Mock method. Water demand is calculated for the projected domestic and non-domestic water needs for 20 years using the exponential method. The results showed that the current storage capacity of the Pajintan reservoir is only sufficient to meet the water needs of the Singkawang Barat and Singkawang Tengah sub-districts for 5% of the total water demand. The area around the Pajintan reservoir which has not yet been developed into a reservoir has an area of 52 hectares. This has the potential to increase the capacity of water availability by building a storage pond so that it can be used as a means of increasing water supply in Singkawang City. Keywords: water demand, water supply, Pajintan Reservoir, Sibuhe Intake Abstrak Kota Singkawang mengalami kekurangan air bersih saat musim kemarau, terutama di daerah bantaran sungai. Embung Pajintan disiapkan untuk dapat digunakan sebagai sumber air baku bagi Kota Singkawang. Penelitian ini bertujuan untuk mengkaji penambahan kapasitas air baku pada IPA Roban untuk pemenuhan kebutuhan air bersih di Kota Singkawang pada musim kemarau. Data yang digunakan adalah data curah hujan dan iklim dari tahun 2003 sampai dengan tahun 2017. Debit sungai diukur di intake Sibuhe. Ketersediaan air di daerah tangkapan air Sibuhe dihitung dengan menggunakan metode Mock. Kebutuhan air dihitung untuk kebutuhan air domestik dan non domestik yang diproyeksikan untuk 20 tahun dengan metode eksponansial. Hasil penelitian menunjukkan bahwa kapasitas tampungan embung Pajintan saat ini hanya cukup untuk memenuhi kebutuhan air di Kecamatan Singkawang Barat dan Kecamatan Singkawang Tengah sebesar 5% dari total kebutuhan air. Kawasan di sekitar embung Pajintan yang masih belum terbangun menjadi embung memiliki luas sebesar 52 Ha. Hal ini sangat berpotensi untuk menambah kapasitas ketersediaan air dengan membangun kolam tampungan agar dapat dimanfaatkan sebagai sarana peningkatan penyediaan air di Kota Singkawang. Kata kunci: kebutuhan air, ketersediaan air, Embung Pajintan, intake Sibuhe